Os programas de descentralização e transferência de responsabilidade na escola pública: Autonomia ou Centralização? - Pires, Edivânia de Castro (2017)
This research aimed at analyzing the conceptions of autonomy, decentralization, quality and training, carried out in the programs of the Education Development Plan, highlighting the participation of the practice context of the Santa Rita-PB Municipal Teaching Network, in a process of experienced correlation of forces teachers in their struggle for public education and better working conditions. Considering that the policy needs to be understood from its context, Ball's Policy Cycle and collaborators were used. In this way, we analyzed the conjuncture in which the policies of decentralization were initiated and how the political discourses established the production of politics. We also analyzed the effects of decentralization policies in the context of practice, with schools as the field. The limits, expectations and perceptions about the programs that are at the center of the EDP in the school were observed through the teaching approach. The research in a qualitative approach, used like procedures the bibliographical analysis, documentary, semistructured interviews and questionnaires. As theoretical foundations it was reported to the studies of Hermida (2008); Saviani (2007, 2009); Camini (2013); Peroni (2003); Souza (2003); Adrião; Peroni (2007); Oliveira (2009); Gentili (1996); Oliveira (2013); Ball (2016); Freitas (2016); Dourado (2009), among others. Through this study, it was possible to perceive that the policies of decentralization and promotion of autonomy, expressed in the Plan of Development of Education, are configured as deconcentrative policies of action, in a managerialist, performative and stateresponsibility perspective, transferring to the school and its actors responsible for the failure of the institution, collaborating and deepening the neoliberal trend implemented in Brazil since the 1990s. Keywords: Decentralization. Autonomy. Accountability. Quality of education.